Detection of Nitric Oxide by Electron Paramagnetic Resonance Spectroscopy - Hogg, Neil (2010)
Electron paramagnetic resonance (EPR) spectroscopy has been used in a number of ways to study nitric oxide chemistry and biology. As an intrinsically stable and relatively unreactive diatomic free radical, the challenges for detecting this species by EPR are somewhat different than those for transient radical species. This review gives a basic introduction to EPR spectroscopy and discusses its uses to assess and quantify nitric oxide formation in biological systems.